Kajian Terhadap Wewenang Diskresi Penyidik Untuk Memilih Dan Menentukan Ahli Pornografi - Ismu Gunadi Widodo (Fakultas Hukum Universitas Bhayangkara Surabaya, 2010)
Based on discretion authority to legality of an act which has been done, investigator must base on rule of code or law The meaning of discretion authority is input of legality to act as a Indonesian Police (POLRI) as investigator to carry on investigating duty, for instance accident case in the traffic. Pro Justice take the main role in investigating, arresting, in prison, researching conviscate and others investigate based on discrete authority.